Research on In Situ Stress Measurements in Reinforced Concrete Beams Based on the Core-Drilling Method - Nian-Chun Deng; Peng-Fei Tang (Advances in Civil Engineering)
To increase the accuracy of the core-drilling method in measuring the in situ stresses within concrete beams, this paper developed a special core-drilling machine system, studied the surface stress release rule of concrete beams through finite element simulations, and then carried out verification tests. The effects of the borehole diameter, drilling depth, strain sensor size, and borehole position on the measurement accuracy were studied. The results showed that borehole diameters of 100 mm, 75 mm, and 50 mm can achieve stress release and that the smaller the borehole diameter was, the easier it was to release the stress. When using the smallest borehole, the stress concentration range around the borehole was narrow, and there was little damage to the original structure. The strain gauge size influenced the actual measurement results. An excessively large strain gauge will be disturbed by drilling because of the limited size of the borehole. An excessively small strain gauge will be easily influenced by the inhomogeneity and randomness of the concrete materials, resulting in large measurement error. The difference between the measured concrete stress and the theoretical value was less than 10%, and the average error was only 6.03%, indicating the feasibility of the proposed method.